International Students' WeChat Use, Prior Cross-Cultural Exposure, Social Self-Efficacy and Cross-Cultural Adaptation in China - Kai, Zhang (Universiti Malaysia Sarawak, 2025)
Previous research indicates that the cross-cultural adaptation of international students in China is influenced by WeChat and social self-efficacy. Cross-cultural exposure has also been found to influence cross-cultural adaptation in other contexts. However, the mechanisms for these causal relationships are unclear . This study examined the indirect relationship between WeChat use and cross-cultural adaptation among Chinese international students by testing a moderated mediation model. Questionnaire data were collected from 404 international students in four universities in western China. The results show that international students in China have a high level of WeChat use, social self-efficacy, and cross-cultural adaptation, and a moderate level of prior cross-cultural exposure. The Pearson correlation tests showed a significant high correlation among the international students’ WeChat use, social self-efficacy, and cross-cultural adaptation. There was a low but significant correlation between prior cross-cultural exposure and WeChat use, social self-efficacy, and cross-cultural adaptation. Regression analyzes showed that there were indirect influences between WeChat use and cross-cultural adaptation among international students in China. Social self-efficacy has a partial mediating effect. Cross-cultural exposure moderates the base level of their cross-cultural adaptation. If WeChat use is set aside, the international students also experience better cross-cultural adaptation when they have high social self-efficacy. The study indicates that there is a mediating influence pathway of social self-efficacy in the association between WeChat use and cross-cultural adaptation, and that this mediating process is further moderated by prior cross-cultural exposure. The study shows that it is important to have prior-departure programmes to give prospective international students cross-cultural exposure and build their social confidence and competence in handling social interactions in a new environment.